High-Risk Factors for Hemorrhage in Hysteroscopic Curettage for Cesarean Scar Pregnancy - Qing Yang; Xiaodie Xiang; Cong Li (Clinical and Experimental Obstetrics & Gynecology)
Background: With the increase in cesarean sections, the occurrence of cesarean scar pregnancies has shown a significant upward trend. To investigate the high-risk factors for hemorrhage during hysteroscopy for cesarean scar pregnancy (CSP). Methods: This is a retrospective case-control study. A total of 338 cases of CSP were divided into-hemorrhage group and non-hemorrhaged group according to the volume of hemorrhage. The collected data included maternal age, duration of amenorrhea, frequency and interval time of cesarean sections, number of induced abortions, pre-treatment human chorionic gonadotropin (hCG) levels, gestational sac length, myometrial thickness at the uterine scar, blood flow signal around the gestational sac as detected by ultrasound, and CSP classification. Statistical analysis was performed to assess differences between the two groups. Results: Statistically significant differences between the two groups were observed in the duration of amenorrhea, gestational sac length, myometrial thickness at the uterine scar, and blood flow signal around the gestational sac. Hysteroscopic curettage for CSP was found to be safe and feasible when the duration of amenorrhea was <49 days, the gestational sac length was <30 mm, the resistance index (RI) of the blood flow signal around the gestational sac was >0.4, and the myometrial thickness at the uterine scar was >2 mm. Conclusions: Hysteroscopic curettage is a safe and effective procedure for CSP in carefully selected patients.